2019
DOI: 10.1186/s12881-019-0931-7
|View full text |Cite
|
Sign up to set email alerts
|

LRCH1 polymorphisms linked to delayed encephalopathy after acute carbon monoxide poisoning identified by GWAS analysis followed by Sequenom MassARRAY® validation

Abstract: BackgroundWe explored the association of leucine-rich repeats and calponin homology domain containing 1 (LRCH1) gene polymorphisms with genetic susceptibility to delayed encephalopathy after acute carbon monoxide poisoning (DEACMP), which might provide a theoretical basis for the pathogenesis, diagnosis, and prognosis research of DEACMP.MethodsFour single nucleotide polymorphisms, rs1539177 (G/A), rs17068697 (G/A), rs9534475 (A/C), and rs2236592 (T/C), of LRCH1, selected as candidate genes through genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 17 publications
0
5
0
Order By: Relevance
“…The study confirmed that two SNPs (rs11845632, rs2196447) in axon protein 3 gene (NRXN3) correlated with DEACMP [ 18 ] and that there was a correlation between rs1784594 in the Parkin gene and DEACMP. We also found that allele A of rs1784594 may increase the risk of DEACMP in female ACMP patients [ 25 ], that LRP1B gene rs1541976 polymorphism is a potential susceptible factor of DEACMP [ 26 ], and that LRCH1 (rs1539177, rs17068697, rs9534475, and rs2236592) is associated with DEACMP [ 27 ]. These results suggest that some ACMP patients are specifically sensitive to acute carbon monoxide poisoning due to polygenic defects, which leads to the initiation of a central nervous system's autoimmune response that attacks the corresponding target cells, leading to the relevant clinical changes.…”
Section: Discussionmentioning
confidence: 99%
“…The study confirmed that two SNPs (rs11845632, rs2196447) in axon protein 3 gene (NRXN3) correlated with DEACMP [ 18 ] and that there was a correlation between rs1784594 in the Parkin gene and DEACMP. We also found that allele A of rs1784594 may increase the risk of DEACMP in female ACMP patients [ 25 ], that LRP1B gene rs1541976 polymorphism is a potential susceptible factor of DEACMP [ 26 ], and that LRCH1 (rs1539177, rs17068697, rs9534475, and rs2236592) is associated with DEACMP [ 27 ]. These results suggest that some ACMP patients are specifically sensitive to acute carbon monoxide poisoning due to polygenic defects, which leads to the initiation of a central nervous system's autoimmune response that attacks the corresponding target cells, leading to the relevant clinical changes.…”
Section: Discussionmentioning
confidence: 99%
“…The score is proportional to cognitive function. Illiteracy <16, secondary school or above <24, primary school <20 points with cognitive impairment [5][6][7] .…”
Section: Score Standardmentioning
confidence: 99%
“…SNPs in LRCH1 have been associated with a higher risk to develop osteoarthritis, although not all studies could confirm these findings (Spector et al, 2006;Snelling et al, 2007;Jiang et al, 2008;Panoutsopoulou et al, 2017). SNPs in LRCH1 are also allocated to an increased risk of delayed encephalopathy after acute carbon monoxide poisoning (Gu et al, 2019). Pigs with SNPs in LRCH3 are more susceptible to infections with Escherichia coli (E. coli) and cows with SNPs in LRCH3 have a higher susceptibility to Mycobacterium avium ssp.…”
Section: Genomic Analysesmentioning
confidence: 99%